Development of a metagenomic DNA extraction procedure and PCR detection of human enteric bacteria in vegetable salad tissues - Panigrahy, Amaresh; Babu, S.; Vivekanandhan, G.; Subashkumar, R.; Thayumanavan, Tha. (Research in Biotechnology, 2011)
Outbreaks of illness due to human enteric pathogenic bacteria via fresh vegetables warrant intensive research on changing strategies of these bacteria in alterning their hosts for survival. The systemic infection of human pathogenic bacteria in plants and the plant growth stage at which they establish endophytic relationship is poorly understood. Since cucumber and carrot are major vegetables consumed in the form of unprocessed salads in India, our study aimed at determination of infection abilities of Salmonella enterica sub sp. enterica and Aeromonas hydrophila in carrot and cucumber, respectively based on a metagenomic detection system. We report an optimized metagenomic DNA isolation procedure from vegetable tissues co-cultivated with bacteria under laboratory conditions. Colonization of bacteria in vegetable tissues was studied by amplification of bacterial 16S rRNA coding region from the metagenome. DNA obtained from carrot vegetable pieces inoculated with Salmonella resulted in expected amplification of 1.2 kb region of bacterial 16S rRNA source sequences. However, the approach failed to detect Aeromonas in cucumber tissues. We conclude that carrot could be a symptomless alternate host for Salmonella sp.